Violation of Cooperation Principles in Drama Ahlul Kahfi the Work of Taufiq Al-Hakim, Analysis of Grice Implicatures (Jurnal Adabiya, 2023)
This study aims to describe the forms of violation of the principles of cooperation in the first part of the Ahlul Kahfi drama. And knowing the conditional meaning of implicature in the first part of the ahlul kahfi drama. To achieve this goal, descriptive qualitative research is used by analyzing and collecting the script of the play in the form of conversations between characters using the theory of violation of the principle of Grice's cooperation which gave birth to the conversational implicature. This method can provide a conclusion that in the script of the first part of the Ahlul Kahfi drama there are several violations  against the principles of cooperation namely the violation of quality maxims, violations of quantity maxims and violations of relationship maxims, and there is no violation of the maxim of means. And the meaning born of the implicature of the conversation due to the violation of the principle is adapted to the context of the speech.